Organizational Commitment as an Antecedent of Organizational Citizenship Behavior: A Study of Nursing Staff Working in Select Government Hospitals in Sidama Regional State, Southern Ethiopia - Anisa, Mengistu; Malhotra, Meenakshi (Gyan Management Journal, 2023)
Successful organizations have employees who go beyond their formal job tasks and freely give their time and liveliness to succeed at the assigned job. Such humanity is neither prescribed nor required, yet it contributes to the smooth functioning of the organization. This study aimed to examine organizational commitment as an antecedent of Organizational Citizenship Behavior a study of nursing staff working in Select Government Hospitals in Sidama Regional State, Southern Ethiopia. Methodologically, the study has been mainly depending on the primary source of data obtained through nursing staff work in the Sidama regional state of southern Ethiopia. Among 1900 total nursing staff in the four hospitals in this study 210 samples have been considered for the analysis based on 204 of the respondents who responded to the questionnaire. In this study, SPSS and AMOS version 21 were applied for analysis purposes. The measurement model based on CFA reveals that the items are fitted for the construct after some of the items are removed as a result of low loadings. The structural equation model shows the positive relationship between the variables under the study. Based on the finding obtained theoretical and practical implications provided through the management of the hospitals need to have enhanced organizational commitment of nursing staff to reciprocate the result. Furthermore, the study opts for future researchers based on the gap mentioned.